Sanksi Hukum Bagi Pelaku Aksi Premanisme yang Dilakukan Ormas Terhadap Petugas Polisi Pamong Praja di Denpasar - I Kadek Anom Suartama; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2024)
The acts of thuggery that usually occur in Denpasar are carried out in groups and organized. The presence of thugs in the area of trade centers, terminals and highways which are often public places is one of the obstacles for the community in carrying out their activities. The formulation of the problems in this study are Factors causing the occurrence of mass organization thuggery acts in Denpasar and Criminal sanctions for perpetrators of thuggery committed by mass organizations against civil service police officers in Denpar, this study uses an empirical legal. Based on the research results, the causes of thuggery include economic and environmental problems. Criminal sanctions for thuggery perpetrators committed by mass organizations at the Satpol PP Denpasar are determined on suspicion of fighting government officials who are carrying out state duties and or persecution and or crimes against people's independence. This is as stipulated in Article 211 of the Criminal Code, Article 212 of the Criminal Code, Article 214 of the Criminal Code and/or Article 351 of the Criminal Code and/or Article 335 of the Criminal Code